La arquitectura de las aplicaciones móviles basadas en el entorno de programación java y su aporte con la seguridad y eficiencia en las actividades de los usuarios de telefonía móvil; caso práctico desarrollo de un software de transformación de mensajes de texto SMS a mensajes de voz y viceversa. - Caguana Lliquin, Alfonso Guido (2013)
The present research work consists in the description and analysis of mobile application architecture based on the Java programming environment and its contribution to the efficiency and security for mobile users. The reason research is to analyze aspects that contemplate the operation of the structure of a mobile application that has become one of the development tools by mobile users, as these applications are useful in the work daily. The problem, on the other hand, the concern is to investigate the factors involved in developing a mobile application.